(untitled) (Research, Society and Development, 2023)
Orofacial harmonization, a specialty of dentistry, aims to improve facial aesthetics and the function of muscles, bones and soft tissues in the mouth and face region. Botulinum toxin plays an important role in this practice, whether applied surgically or not to alleviate problems such as bruxism and chronic pain. The use of botulinum toxin has gained acceptance in dentistry due to its effectiveness in reducing facial muscle tension. For patients with bruxism, botulinum toxin temporarily paralyzes the chewing muscles, relieving pressure on the teeth and reducing tooth wear. Furthermore, it is useful in treating conditions such as temporomandibular disorder (TMD) and tension migraines, providing relief. However, it is essential that orofacial harmonization professionals have anatomical knowledge and clinical experience in procedures with botulinum toxin to ensure safe results. The practice must follow ethical and legal guidelines for the safety and well-being of patients. The integration of botulinum toxin into dentistry, in the context of orofacial harmonization, represents an innovative approach with the potential to improve the health and quality of life of patients facing painful and dysfunctional facial conditions. Therefore, the objective of this narrative review of the literature is to investigate the association of botulinum toxin as a therapeutic option in the practice of orofacial harmonization.